Kemampuan Koneksi Matematis Siswa Ditinjau dari Kemampuan Awal dan Gender - Ita Mafajatul Aliyah; Yuyu Yuhana; Cecep Anwar Hadi Firdos Santosa (Didaktik Matematika, 2019)
This research aimed to examine students mathematical connection ability based on previous ability and gender. The instruments of the study were the researcher as the main instrument, the test of prior knowledge, the test of connection ability, interview and documentation. The triangulation technique was used for the data (test, observation, interview, and documentation). The subject of this research were six students representing each category of the previous ability. Three indicators of mathematical connection ability used in this research, namely: connections between mathematical topics, connections with the science other than mathematics, and connection with life. The results showed that 1) high-ability male subject had high levels of mathematical connection ability on indicators of connection with life, 2) high-ability female subject had high level of mathematical connection ability on indicators of connection with the science other than mathematics, 3) medium-ability male subject had high levels of mathematical connection ability on indicators between topics mathematics, 4) medium-ability female subject had high levels of mathematical connection ability on indicators between topics mathematics, 5) low-ability male subject had high levels of mathematical connection ability on indicators between topics mathematics, 6) low-ability female subject had high levels of mathematical connection ability on indicators between topics mathematics.